Complement Genes Strongly Predict Recurrence and Graft Outcome in Adult Renal Transplant Recipients with Atypical Hemolytic and Uremic Syndrome. Issue 3 (28th January 2013) - Le Quintrec, M.; Zuber, J.; Moulin, B.; Kamar, N.; Jablonski, M.; Lionet, A.; Chatelet, V.; Mousson, C.; Mourad, G.; Bridoux, F.; Cassuto, E.; Loirat, C.; et al.
<x xml:space="preserve">Abstract</x> Atypical hemolytic and uremic syndrome (aHUS) is a severe disease strongly associated with genetic abnormalities in the complement alternative pathway. In renal posttransplantation, few data are available on recurrence risk and graft outcome according to genetic background in aHUS patients. The aim of this study was to identify risk factors for recurrence and transplant outcome and, in particular, the role of complement gene abnormalities. We retrospectively studied 57 aHUS patients who had received 71 renal transplants. A mutation in complement gene was identified in 39 (68%), in factor H (CFH), factor I (CFI), membrane cofactor‐protein (MCP), C3 and factor B (CFB). At 5 years, death‐censored graft survival was 51%. Disease recurrence was associated with graft loss (p = 0.001). Mutations in complement genes were associated with higher risk of recurrence (p = 0.009). Patients with CFH or gain of function (C3, CFB) mutations had a highest risk of recurrence. M‐TOR inhibitor was associated with significant risk of recurrence (p = 0.043) but not calcineurin inhibitor immunosuppressive treatment (p = 0.29). Preemptive plasmatherapy was associated with a trend to decrease recurrence (p = 0.07). Our study highlights that characterization of complement genetic abnormalities predicts the risk of recurrence‐related graft loss and paves the way for future genetically based individualized prophylactic therapeutic strategies.